Agronomic traits of lettuce (Lactuca sativa L.) under different temperatures as influenced by black soldier fly frass and vermicompost derived from kitchen waste (Dhaka University Journal of Biological Sciences, 2025)
Lettuce (Lactuca sativa L.) is an annual leafy herb and one of the most widely consumed salad vegetables. Due to its rich nutritional profile including vitamins, minerals, and folate - it has garnered significant research interest concerning its health benefits and cultivation practices. This study aimed to evaluate the influence of kitchen waste-mediated organic composts on the agronomic traits of lettuce under two distinct temperature regimes. Two pot experiments were conducted in the greenhouse of the University of Dhaka, Bangladesh, at constant temperatures of 22°C and 30°C during December 2023 to February 2024. Each pot was filled with 1.5 kg of processed soil and treated with black soldier fly (BSF) frass and vermicompost (V) at 0%, 25%, and 50% of the soil volume. The experiments ran for 70 days, and agronomic traits such as plant height, number of leaves per plant, leaf length and width, stem girth, and fresh and dry weights were recorded at 20, 45, and 70 days after transplanting (DAT), while root length was measured at final harvest (70 DAT). Results revealed that the higher temperatures (30°C) promoted greater plant height across all treatments compared to 22°C. The number of leaves per plant was significantly affected by compost type and temperature. Leaf dimensions increased progressively with time. The percentage increase over control (IOC) was consistently higher at 22°C across all sampling times, except in the V 50% treatment at 30°C. Dry matter content was also greater at 22°C for all compost levels. The highest fresh (43.4 g and 42.0 g) and dry (2.4 g and 2.2 g) weights were recorded under the V 50% treatment at both temperatures, whereas control pots yielded the lowest values. Overall, the higher dry matter content indicated greater yield potential in lettuce under cooler growing conditions.Dhaka Univ. J. Biol. Sci. 34(2): 13-28, 2025 (July)